Vatiga spp. associadas à mandioca e morfologia e biologia de V. illudens em diferentes genótipos da cultura - Wengrat, Ana Paula Gonçalves da Silva (2016)
Species of Vatiga (Hemiptera: Tingidae) are pests of Cassava, Manihot esculenta Crantz (Euphorbiaceae), an important food source for more than 800 million people. Vatiga infestations in Cassava can cause serious production losses. Although importance economic, there are few research work about morphological description this species, relevant item in pest identification at the beginning of infestation and for use in phylogenetic analysis. Furthermore, not many records occur of Vatiga species and resistant genotypes to prague. That way, has been described and illustred the external morphology all the phases of V. illudens life, evaluated at resistance of five genotypes of cassava at this species and raising the occurence of insects of the genus Vatiga in Cassava comercial crops. About morphology, the eggs´s whitish, oblong-shaped and deposited inside of leaf. Nymphs, the dorsal surface of the head and body side margins have spikes; from the second to fifth instar the cephalic and lateral spikes become more visible, but in least amount that V. manihotae. Genotypic resistance showed that insects supplied Mecu 72 genotype had affected their development, thereby increasing nymphal and eggs-adults period, reducing significantly the fertility. The occurrence of the species recorded four species of Vatiga